The Difference in Cloud Water Resources and Precipitation on the Eastern and Western Sides of the Liupan Mountains Caused by Topographic Effects - Rui Xu; Yujun Qiu (Atmosphere, 2023)
In order to explore the possible impact of topography on precipitation between the eastern and western sides of the Liupan Mountains (LMs) in the northwest region of China, the differences in distribution characteristics of total column water vapor (TCWV), total column cloud water (TCCW), and total precipitation (TP) were studied by using the 40-year hourly data of the fifth generation reanalysis (ERA5) from the European Centre for Medium-Range Weather Forecasts (ECMWF). The results showed the following: (1) The TCCW and TP on the eastern and western sides of the LMs decrease gradually from south to north, following a southwestward bias along the latitude. The high values of the TCCW and TP are predominantly concentrated in the period from July to September. The greatest difference between the two sides occurs in September, with the eastern side exhibiting 15% and 18% higher values compared to the western side, respectively. (2) Both the TCCW and TP exhibit distinct diurnal distribution patterns. The high values on the eastern side persist for a longer duration throughout the day compared to the western side, and they occur in more consecutive months. There is a certain correlation between the steepness of the eastern slope and the gentle gradient of the western slope. Additionally, the occurrence of these high values in the afternoon is earlier on the eastern side compared to the western side. (3) The monthly mean TP is significantly linearly correlated with the TCWV and TCCW, with slightly higher coefficients for the western side compared to the eastern side. This relationship is closely related to the topography of the mountain range. The regression equation provides a quantitative tool for predicting the monthly mean TP in the LM region and serves as a reference basis for the development of cloud water resources in the area.